Age, origin and tectonic setting of Dulaankhan granitic pluton in northern Mongolia - Gendenjamts, Baatar; Munkhtsengel, Baatar; Odgerel, Dashdorjgochoo; Sanchir, Dorjgochoo; Ganbat, Bayaraa (Mongolian Geoscientist, 2019)
Dulaankhan granitic pluton, which is situated in northern Mongolia, the southern portion of the Mongolian-Transbaikalian belt (MTB), is petrographically composed of fine to medium-grained peralkaline granite and is intruded by a small body of quartz syenite. Geochemical data show the Dulaankhan granite and the intruding quartz syenite are both slightly peraluminous and high-K calc-alkaline, and are enriched in LREEs relative to the HREEs, with negative Eu anomaly, and in large ion lithophile elements (LILEs; such as K, Cs and Rb) with respect to high field strength elements (HFSEs; e.g., Nb, Ta and Ti). In terms of relations of Nb, Zr and Y to Ga/Al, however, the Dulaankhan granite and quartz syenite show geochemical features of A-type granites and can be classified into the A2-sub type granite, implying that the pluton formed in an post-collision extensional environment. LA-ICPMS zircon U-Pb dating results suggest that the Dulaankhan granite crystallized at 198±1 Ma, whereas the intruding quartz syenite at 180±1 Ma, consistent with our field observation that the quartz syenite intrudes the granite, attesting that the two granitic bodies were emplaced at different times although both of them formed during the Early Jurassic period. According to these new data, as well as regional ones, we propose that the Dulaankhan granitic pluton was likely generated in the post-collision setting related to the orogenesis of the Mongol-Okhotsk belt that seems to occur prior to Early Jurassic in the northern Mongolian segment.